Mesenchymal Stem Cell-Derived Exosomes: Biological Function and Their Therapeutic Potential in Radiation Damage - Xiaoyu Pu; Siyang Ma; Yan Gao; Tiankai Xu; Pengyu Chang; Lihua Dong (Cells, 2020)
Radiation-induced damage is a common occurrence in cancer patients who undergo radiotherapy. In this setting, radiation-induced damage can be refractory because the regeneration responses of injured tissues or organs are not well stimulated. Mesenchymal stem cells have become ideal candidates for managing radiation-induced damage. Moreover, accumulating evidence suggests that exosomes derived from mesenchymal stem cells have a similar effect on repairing tissue damage mainly because these exosomes carry various bioactive substances, such as miRNAs, proteins and lipids, which can affect immunomodulation, angiogenesis, and cell survival and proliferation. Although the mechanisms by which mesenchymal stem cell-derived exosomes repair radiation damage have not been fully elucidated, we intend to translate their biological features into a radiation damage model and aim to provide new insight into the management of radiation damage.